Integration of Language and Mathematical Intelligence in Improving Elementary School Students' Literacy - Sitompul, Ismaini; Rais, Muhammad Amien; Sitompul, Nurul Hadawiyah (Cendekiawan : Jurnal Pendidikan dan Studi Keislaman, 2025)
Elementary school students' literacy levels are often separated between language skills and mathematical reasoning, resulting in partial and less impactful improvement efforts. This research aims to systematically examine evidence on the integration of language and mathematical intelligence to improve elementary school students' literacy. The method used was a systematic literature review (SLR) based on PRISMA guidelines, searching Scopus, WoS, ERIC, and Google Scholar databases with combinatorial keywords such as "language intelligence," "mathematical reasoning," "integrated literacy," and "elementary students" for the period 2014–2025. Inclusion criteria included empirical studies in elementary education, language-mathematics integration interventions or models, and reporting of literacy learning outcomes; exclusion criteria included non-empirical studies and educational levels beyond elementary school. Selection was carried out in stages (identification, duplication screening, abstract title screening, full review), followed by quality assessment using the Mixed Methods Appraisal Tool (MMAT) checklist. Data were extracted and synthesized through a narrative thematic mapping of intervention design, task modalities, outcome metrics, and implementation conditions. Results demonstrate consistent improvements in inferential understanding, translation across textual representations of graphs, tables, and evidence-based argumentation, particularly in the design of authentic multimodal tasks that orchestrate reading, reasoning, writing, and arithmetic. Consequently, this integration strengthens reading and numeracy literacy while fostering early data literacy; practical implications emphasize an integrated thematic curriculum, teacher capacity building for multimodal tasks, and integrated formative assessment that captures both the process and the product of learning.